Automatic Shift Control of an Electric Motor Direct Drive for an Electric Loader - Cai, Shaole; Chen, Qihuai; Lin, Tianliang; Xu, Mingkai; Ren, Haoling (Machines (Basel), 2022)
Traditional loaders with engines present the drawbacks of high energy consumption and poor emissions performance. The usage of an electric motor instead of an engine in an electric loader can effectively improve energy efficiency and emissions. The loader is mainly used in the earthwork construction of unstructured roads. Compared to the automobile, during the working process of the loader, the load fluctuates violently, and the vibration is serious. A large torque range during operation, a wide speed range during transfer, and frequently switching gears to ensure power are required by the loader. Therefore, the automatic shift control strategy for an automobile cannot be well applied to the loader directly. In this paper, a novel distributed electric motor-driven loader in which the walking drive system and the hydraulic system is decoupled is studied. The shift rule of the electric loader is also studied. A comprehensive automatic shift control strategy considering power and economy is proposed. Simulations are carried out to verify the feasibility of the proposed control strategy. The results show that under the “V” cycle operation condition of the loader, the shift rule meets the control requirements and the shift effect is obvious and reasonable. In terms of transfer conditions, the proposed control strategy yields ideal power performance and energy savings.